2012
DOI: 10.1146/annurev-cellbio-100809-151736
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Organizing Principles of the Plasma Membrane that Regulate Signal Transduction: Commemorating the Fortieth Anniversary of Singer and Nicolson's Fluid-Mosaic Model

Abstract: The recent rapid accumulation of knowledge on the dynamics and structure of the plasma membrane has prompted major modifications of the textbook fluid-mosaic model. However, because the new data have been obtained in a variety of research contexts using various biological paradigms, the impact of the critical conceptual modifications on biomedical research and development has been limited. In this review, we try to synthesize our current biological, chemical, and physical knowledge about the plasma membrane to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
507
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(520 citation statements)
references
References 224 publications
13
507
0
Order By: Relevance
“…3). A function of the PM-MT nexus for subdomain formation is further supported by studies in yeast also in S. cerevisiae (Kusumi et al, 2012). In addition, the plant PM-MT interface plays important roles in cell wall biogenesis and cell shape regulation, mainly by guiding the deposition of nascent cellulose fibers.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…3). A function of the PM-MT nexus for subdomain formation is further supported by studies in yeast also in S. cerevisiae (Kusumi et al, 2012). In addition, the plant PM-MT interface plays important roles in cell wall biogenesis and cell shape regulation, mainly by guiding the deposition of nascent cellulose fibers.…”
Section: Discussionmentioning
confidence: 85%
“…Lateral stability is a hallmark of membrane subdomains, and their stabilization within the PM requires scaffolding functions of the cytoskeleton (Kusumi et al, 2012). Colocalization with RFP-TUA5 revealed that the PM subdomains labeled by GFP-tagged IQD proteins partially align along MT arrays (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Membrane lipids contribute to cell signaling directly, by acting as precursors to signaling molecules (19), and indirectly, by controlling the spatiotemporal organization of signaling proteins through the formation of ordered membrane domains rich in saturated sphingolipids, glycerophospholipids, and cholesterol (20)(21)(22)(23). Often referred to as lipid rafts, these microdomains are less fluid, condensed regions within the membrane that affect protein diffusion and compartmentalize signaling processes (20)(21)(22)(23). Thus, the lipid composition and degree of fatty acid saturation present within the cell membrane are thought to influence membrane fluidity and, in turn, T cell signaling (24).…”
mentioning
confidence: 99%
“…PM composed of proteins and lipids regulates cell signaling and many other cellular processes through its unique "dynamic, yet structured" feature (Vereb et al 2003;Escribá et al 2008;Kusumi et al 2012;Török et al 2014). According to the fluid mosaic model proposed by Singer and Nicolson in 1972, the PM has a two dimensional phospholipid bilayer, hosting membrane proteins which are dispersed randomly and homogenously within the lipid bilayer.…”
Section: Alterations In Lipid Membranesmentioning
confidence: 99%
“…They reported that the actin based membrane skeleton as "fence" and transmembrane proteins as "pickets" hinder the diffusion rate of membrane molecules (Kusumi et al 2012). Bilayer heterogeneity can be explained by introducing the term of membrane microdomains (also called rafts).…”
Section: Alterations In Lipid Membranesmentioning
confidence: 99%